Analysis of Lecturer Competency and Knowledge in Technopreneurship Development of Student MSMEs in PTS - Hamsinah, Hamsinah; Rusilowati, Umi; Sunarsi, Denok (Pandawan, 2024)
This study looks at how technopreneurship and its consequent function in assisting the growth of student Micro, Small, and Medium Enterprises (MSMEs) at private institutions in the Banten region are impacted by the knowledge management and skills of lecturers. The goal of the study is to better understand how these elements interact to improve technology focused entrepreneurship education. Using a survey methodology and probability sampling, a quantitative approach was used to gather data from 397 students attending private universities in Banten. Version 3.0 of the Partial Least Squares (PLS) software was used to analyze the data. The findings show that: (1) knowledge management has a significant and positive impact on technopreneurship (t-statistic of 95.378 > t-table 1.649 and a P-value of 0.00 < 0.05); (2) competence has a significant and negative impact on technopreneurship (t-statistic of 7.386 > t-table 1.649 and a P-value of 0.000 < 0.05); (3) knowledge management has no significant effect on MSME development (t-statistic of 0.974 < t-table 1.649 and a P-value of 0.330 > 0.05); (4) competence similarly has no significant effect on MSME development (t-statistic of 0.639 < t-table 1.649 and a P-value of 0.523 > 0.05); and (5) technopreneurship has a significant positive effect on MSME development (t-statistic of 34.058 > t-table 1.649 and a P-value of 0.000 < 0.05).